Spatial and temporal responses of swamp wallabies to roads in a human‐modified landscape. Issue 2 (8th June 2021) - Fischer, Manuela; Stillfried, Milena; Coulson, Graeme; Sutherland, Duncan R.; Kramer‐Schadt, Stephanie; Stefano, Julian Di
Abstract : Roads can have significant impacts on wildlife populations by impeding movement, restricting access to resources and causing wildlife–vehicle collisions. In particular, wildlife–vehicle collisions represent a substantial conservation and social problem, and although mitigation measures are available, an increased understanding of the temporal and spatial patterns of animal movement around roads will enhance their effectiveness. We analysed GPS telemetry data from 47 swamp wallabies Wallabia bicolor on Phillip Island, south‐east Australia, within patches of native vegetation dissected by roads. Our aims were to determine if (a) road crossing frequency was influenced by time period (day, night) or sex, (b) wallabies avoided roads, and if avoidance was influenced by time period or sex and (c) road crossing locations were associated with dense vegetation, and other habitat characteristics. We found that males crossed roads more often at night than during the day while females showed the opposite pattern. Further, wallabies avoided roads, with some evidence that avoidance increased at night (p = 0.07). The chance of a wallaby crossing roads with high speed limits (80–100 km h‐ 1 ) increased with vegetation density during the day but not at night. In contrast, vegetation density had no influence on crossing locations along roads with lower (50–70 km h‐ 1 ) speed limits during the day or night. Both vegetation density and vehicle speed may influence wallaby–vehicle collisions and suggest management strategies targeting these factors. Partial fencing guiding wallabies towards safer crossing locations, combined with other measures such as reduced speed limits and signage, could reduce collisions between vehicles and swamp wallabies on Phillip Island.